Corpos (con) sentidos: cartografando processos de subjetivação de produto(re)s de corporalidades singulares - Nascimento, Márcio Alessandro Neman [UNESP] (2015)
Disruptions produced by the coexistence of events in (trans)contemporaneity make the insurgent connections between corporeality and lifestyles more complex, being those multiple and strategic points in the process of subjectivation. Experiences, desires, sensations and sensibilities to pleasures as well as the (trans) formations in and by the bodies have set larger contexts of collisions in the field of ethical and aesthetic constructions.These conflicts urge between normalized and normative models and other body projects presented as singular aesthetics - which seek to break with the ordinary, the referenced, the established. In the production of the power-knowledge-pleasure relations, the corporeality extrapolates and crosses its defining and identitary boundaries, bringing forth disorder in the logic of intelligibility, which place us in front of new possibilities to think of more potent epistemologies and methods regarding studies on humans as experimentation projects intersecting with a variety of heterogeneous elements arranged in the social field. Thus, this doctoral research aimed to problematize the insurgency of body singularities production processes and modes of subjectivation resistant to ethical and aesthetic of the dominant matrices. Therefore, we chose the cartography method perspective to analyze the expressions and social practices of so called abject subjects who (de)construct their bodies and (re)assemble inventive and creative aesthetic, often seen as expression of revolt by the disciplined and disciplinarian eye. Conclusive notes brought by the incursion of the social field and by interviews with participants indicated that, although there are subjectivity production lines which remain normalized, it is possible to observe that the techniques of body modification may produce, besides subversive corporealities, resistance to moralist discursive models and possibilities to...